New particles working group teport of the Snowmass 2013 community summer study - Gershtein, Yuri; Bauer, Martin (Arxiv, 2013)
This report summarizes the work of the Energy Frontier New Physics working group of the 2013 Community Summer Study (Snowmass).
Gesehen am 10.01.2018